2021
DOI: 10.1016/j.ijid.2021.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of anakinra for tocilizumab-refractory severe COVID-19: A single-centre retrospective comparative study

Abstract: Objetives A subgroup of patients with SARS-CoV-2 infection is considered to develop a cytokine release syndrome and have been treated with tocilizumab, but a significant percentage of patients evolve. Our objective was to determine the usefulness of anakinra as rescue treatment for patients with tocilizumab-refractory COVID-19 disease. Methods A prospective cohort of patients with COVID19 pneumonia who received anakinra as salvage therapy after failure of tocilizumab we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Which is the optimal pharmacological strategy in patients refractory to Tocilizumab is an unresolved issue. A small sample size study showed no advantage of the IL-1 antagonist Anakinra as rescue treatment in Tocilizumab-refractary patients [38] .…”
Section: Discussionmentioning
confidence: 94%
“…Which is the optimal pharmacological strategy in patients refractory to Tocilizumab is an unresolved issue. A small sample size study showed no advantage of the IL-1 antagonist Anakinra as rescue treatment in Tocilizumab-refractary patients [38] .…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, the CORIMUNO-ANA-1 study reported that Anakinra did not improve outcomes in patients with mild-to-moderate COVID-19 pneumonia [97]. Similarly, a single-center retrospective comparative study was performed by de la Calle et al, which reported that treatment with anakinra was not able to improve the prognosis of patients with tocilizumab-refractory severe COVID-19 [98].…”
Section: Interleukin Targetingmentioning
confidence: 99%
“…In the absence of an effective treatment option against COVID-19, the steadily increased mortality among infected subjects and the delay in the widespread vaccination of the general population, it seems that immunomodulatory agents might be crucial for the management of the disease. However, it remains unclear which one should be preferred, although they could be administered sequentially in refractory cases [3,4].…”
mentioning
confidence: 99%